Impedance spectroscopy diagnostics of spent lithium-ion batteries in recycling processes - Zhigalenok, Ya.S.; Starodubtseva, A.A.; Kan, T.V.; Malik, S.D.; Malchik, F.I. (Chemical Bulletin of Kazakh National University, 2025)
The widespread adoption of electric transportation is leading to the accumulation of spent lithium-ion batteries requiring sorting prior to recycling or reuse. Effective triage of end-of-life (EoL) batteries necessitates rapid non-destructive diagnostic methods capable of assessing the state of health at the individual cell level. This study proposes an approach to rapid diagnostics based on electrochemical impedance spectroscopy. Using a 10S6P battery pack from an electric scooter operated under sharply continental climate conditions as an example, we demonstrate that equivalent circuit model parameters – including ohmic resistance, charge transfer resistance, and constant phase element exponents – enable the identification of intra-pack degradation heterogeneity and classification of cells according to their suitability for reuse. Analysis revealed two distinct degradation patterns: localized critical discharge attributed to battery management system malfunction, and a gradient of accelerated aging in peripheral cells due to thermocyclic stress. It was established that 80% of the cells in the investigated pack retain characteristics permitting second-life applications, while 10% exhibit signs of irreversible degradation and require immediate recycling. The results confirm the promise of impedance spectroscopy as a tool for high-throughput triage of EoL batteries within the circular economy framework.